Next-Gen UAV-Satellite Communications: AI Innovations and Future Prospects - Sherief Hashima; Ahmad Gendia; Kohei Hatano; Osamu Muta; Mostafa S. Nada; Ehab Mahmoud Mohamed (IEEE Open Journal of Vehicular Technology)
The convergence of sixth-generation (6G) networks with unmanned aerial vehicles (UAVs) and satellites is poised to introduce substantial improvements to the landscape of wireless communication, paving the way for a unified and uninterrupted space-air-ground-sea network that ensures comprehensive global connectivity. At the heart of this transformative paradigm lies artificial intelligence (AI), which drives innovation across diverse sectors by enhancing decision-making autonomy, enabling real-time data processing, and optimizing network performance and coverage. This survey paper explores AI-enabled UAV-satellite communications for 6G applications, focusing on its challenges, potential, and future. This new system combines the strengths of 6G networks, UAVs (advanced drones), and satellites. It opens up new possibilities in precision agriculture, disaster management, enhanced telecommunication services, and remote sensing. Despite its promise, this field faces complex challenges. These include spectrum management, security risks, regulatory barriers, and integrating AI operations seamlessly. This paper comprehensively analyzes these challenges, offering innovative solutions and outlining future research directions to unlock the complete capabilities of 6G-enabled UAV-satellite communications. Furthermore, it includes a case study demonstrating the effectiveness of multi-armed bandit (MAB) algorithms in optimizing resource allocation and decision-making processes for UAV-low Earth orbit (LEO) satellite communication scenarios, showcasing significant improvements in network performance. This work lays the foundation for a new generation of ultra-connected, data-driven applications that will redefine global connectivity and technological advancement by addressing these critical aspects.